Penggunaan Model Inquiry Learning dan Pengaruhnya terhadap Scientific Attitude Pada Pembelajaran IPA Kelas V Sekolah Dasar - Utaminingtyas, Siwi; Evitasari, Atika Dwi (Edukasi: Jurnal Penelitian dan Artikel Pendidikan, 2021)
This research consists of 2 variables, namely the inquiry learning model and scientific attitude. The purpose of this study was to determine whether the inquiry learning model had an effect on the scientific attitude of students in science subjects for class V. This research method used library research. Sources of data in this study in the form of books, theses and journals from previous research. Inquiry learning model is a learning model that involves the maximum ability of students to search and investigate systematically, critically, logically, and analytically, so that students can formulate their own findings with confidence. Scientific attitude or scientific attitude is a person's behavior that arises because of a stimulus in the form of a good attitude based on existing experience so that it makes a person more sensitive to the surrounding environment and can solve existing problems by using the skills he has. By using the inquiry learning model, it has a positive influence on scientific attitudes and student learning outcomes in science subjects on the properties of light.